THE ROLE OF MELATONIN DEFICIENCY IN THE GENESIS OF ARTERIAL HYPERTENSION IN PATIENTS WITH CHRONIC KIDNEY DISEASE - Anna Petrova; Olena Karpenko (Bogomolets National Medical University, 2020)
The study analyzed the prevalence of hypertension and impaired melatonin-forming function of the epiphysis in patients with stage 5 chronic kidney disease treated with hemodialysis. The relationship between epiphysis dysfunction and hypertension has been identified. 130 persons (50% of men) undergoing permanent hemodialysis treatment were examined. Controls were 20 healthy individuals. The determination of daytime and nighttime levels of melatonin in saliva and clinical and laboratory studies. As a result of the study it was found that for patients with stage 5 chronic kidney disease undergoing treatment, there is a frequent violation of melatonin-forming function of the pineal gland (84.6%) and hypertension (78%). In hemodialysis patients, blood pressure increases are age-dependent and are determined with salivary melatonin levels.